2013
DOI: 10.1371/journal.pone.0081661
|View full text |Cite
|
Sign up to set email alerts
|

Recipe for a Busy Bee: MicroRNAs in Honey Bee Caste Determination

Abstract: Social caste determination in the honey bee is assumed to be determined by the dietary status of the young larvae and translated into physiological and epigenetic changes through nutrient-sensing pathways. We have employed Illumina/Solexa sequencing to examine the small RNA content in the bee larval food, and show that worker jelly is enriched in miRNA complexity and abundance relative to royal jelly. The miRNA levels in worker jelly were 7–215 fold higher than in royal jelly, and both jellies showed dynamic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
74
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(79 citation statements)
references
References 68 publications
(84 reference statements)
5
74
0
Order By: Relevance
“…We previously showed that miRNAs in jellies could influence the caste determination of worker and queen bee larvae (Guo et al 2013). Here, we have profiled the small RNAs of fourth to sixth day worker and queen larvae using deep sequencing and qRT-PCR to explore the mechanism of caste determination and found that 53 known miRNAs were expressed in the early and critical caste developmental stages of bees, a number of which were shown higher in either queen or worker larval bees than the others, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We previously showed that miRNAs in jellies could influence the caste determination of worker and queen bee larvae (Guo et al 2013). Here, we have profiled the small RNAs of fourth to sixth day worker and queen larvae using deep sequencing and qRT-PCR to explore the mechanism of caste determination and found that 53 known miRNAs were expressed in the early and critical caste developmental stages of bees, a number of which were shown higher in either queen or worker larval bees than the others, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…To analyze the miRNA expression levels at different developmental stages (day 4, day 5, day 6) in workers and queens, the ΔCT values for different developmental stages were calibrated against the respective CT value of the day 4 sample in queens. qPCR results are presented as the fold expression relative to the day 4 sample in queens as performed in other study (Guo et al 2013) unless otherwise stated.…”
Section: Measurement Of the Expression Levels Of Mirnas By Quantitatimentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, bee-derived miRNAs may be transferred to larval honey bees via inoculation of royal jelly with miRNAs by adult nurse bees, leading to specific effects on gene expression during larval development. 71,72 In theory, packaging could also occur in a manner that has been selected for cross-kingdom communication. In addition, incidental inclusion of miRNA into exosomes or cell-free ribonucleoprotein complexes will occur during the processes of digestion.…”
Section: Introductionmentioning
confidence: 99%